2006
DOI: 10.1016/j.jcrs.2006.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Triamcinolone acetonide suspension toxicity to corneal endothelial cells

Abstract: Commercial TA suspension was cytotoxic to cultured rabbit CECs because of the preservative, BA, in the vehicle. Because 1/10 -vTA appeared to be safe for up to 30 minutes of exposure, use of 1/10 dilutions of vehicle-removed TA is suggested to help surgeons visualize prolapsed vitreous during anterior vitrectomy in complicated cataract surgeries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…In several studies, the preserved form of commercial triamcinolone acetonide suspension caused damage to human and rabbit retinal pigment epithelial cells, 17 rabbit corneal endothelial cells, 18 and to proliferating cells of retinal origin in vitro at doses normally used in clinical practice. 19 Vehicle-free triamcinolone acetonide suspensions do not seem to damage human retinal pigment epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In several studies, the preserved form of commercial triamcinolone acetonide suspension caused damage to human and rabbit retinal pigment epithelial cells, 17 rabbit corneal endothelial cells, 18 and to proliferating cells of retinal origin in vitro at doses normally used in clinical practice. 19 Vehicle-free triamcinolone acetonide suspensions do not seem to damage human retinal pigment epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…8 Oh et al 9 applied TA intracamerally into rabbit eyes to investigate the effect of TA on the corneal endothelium and showed reduced microvilli, although no statistically significant differences in endothelial counts and central corneal thickness were observed at 2 h after the experimental procedure. Chang et al 10 showed toxicity of TA on cultured endothelium in their experimental study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Published studies have reported varied incidences of ocular hypertension secondary to triamcinolone use, ranging from 21% after sub-Tenon's injections [3][4][5] to 56% after intravitreal injections. 10,22,23 In addition to the risk of increased IOP due to triamcinolone use, pseudophakic children face a greater risk of developing ocular hypertension and glaucoma after the congenital cataract surgery itself, 11,12 which has been reported in up to 24.4% of patients. 12 There was no significant difference in the mean CCT before and after surgery in the current study.…”
Section: Discussionmentioning
confidence: 99%